2011
DOI: 10.1515/cclm.2011.675
|View full text |Cite
|
Sign up to set email alerts
|

The value of serum ischemia-modified albumin for assessing liver function in patients with chronic liver disease

Abstract: IMAR, reflecting liver function and oxidative stress, is a more objective liver function test as it was not affected after a 3-day albumin infusion. More investigations, however, are needed to validate the use of IMAR in cases of chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 21 publications
3
23
0
3
Order By: Relevance
“…There are concerns about tissue-specificity of IMA, as it has been suggested that IMA is a biomarker for other oxidative stress or ischemia-related diseases 19. The possible role of IMA was confirmed in previous studies 4,6,1012. In the present study, the T2DK patients had significantly poorer glycemic control, which was associated with an increase in inflammatory and oxidative stress biomarkers.…”
Section: Discussionsupporting
confidence: 82%
“…There are concerns about tissue-specificity of IMA, as it has been suggested that IMA is a biomarker for other oxidative stress or ischemia-related diseases 19. The possible role of IMA was confirmed in previous studies 4,6,1012. In the present study, the T2DK patients had significantly poorer glycemic control, which was associated with an increase in inflammatory and oxidative stress biomarkers.…”
Section: Discussionsupporting
confidence: 82%
“…Mentese et al (30) reported that IMA was an appropriate ischaemiareperfusion injury marker of testicular damage during acute and chronic periods. In addition, IMA was reported to be an important indicator of liver function (10). We also observed that the antioxidant RV attenuated IMA levels in parallel with changes in liver enzymes and bilirubin.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore continuous liver cells damage, leads to a deficiency in the synthesis of cholinesterase enzyme. In agreement with Chen et al (2011) serum cholinesterase is an excellent biomarker of cirrhosis with good sensitivity and specificity. It shows good correlation with serum albumin and PT.…”
Section: Parameter Albumin (G/l) Prothrombin Time (S)supporting
confidence: 56%